La controversia de nación e imperio. Reacción de los pensadores españoles a la Revolución de Holanda (II) - Racionero Carmona, Quintín (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2010)
This paper aims to present a conceptual analysis on the specificity of some nuclear political notions – nation, empire, sovereignty, renovation– such as they were forged within the Spanish intellectual milieu of the XVIth and XVIIth centuries. The political thinking of this period in Spain was unequivocally pressed by the revolt and independency of one part of its territory, the United Provinces, a region quite important due to its intellectual strength, and even more significant in relation to its economic power.